Multiyear Patterns of Serum Inflammatory Biomarkers and Risk of Colorectal Neoplasia in Patients with Ulcerative Colitis. Issue 1 (January 2016) - Koutroubakis, Ioannis E.; Regueiro, Miguel; Schoen, Robert E.; Ramos-Rivers, Claudia; Hashash, Jana G.; Schwartz, Marc; Swoger, Jason; Barrie, Arthur; Baidoo, Leonard; Dunn, Michael A.; Hartman, Douglas; Binion, David G.
Abstract : Background: Patients with ulcerative colitis (UC) are at increased risk of colorectal neoplasia (CRN) presumably because of chronic inflammation. Data on the relationship between long-term serum inflammatory biomarkers and the development of CRN in UC are limited. Methods: We performed a 5-year study (2009–2013) of demographic, clinical, laboratory, and treatment data of patients with UC from an inflammatory bowel disease registry in relation to the development of CRN. Disease activity was evaluated by UC activity index and by serum biomarkers such as C-reactive protein (CRP), erythrocyte sedimentation rate, hemoglobin, platelets, and albumin levels. A score based on the combination of median CRP and median albumin levels (0: both normal, 1: one of them abnormal, 2: both abnormal) was also evaluated. Results: A total of 773 patients with UC (median age 46 yr, 46.4% women) were included. Fifty-five patients (7.1%) developed CRN. Patients with UC and CRN had significantly higher median CRP, erythrocyte sedimentation rate, and platelets and lower hemoglobin and albumin levels compared with those without CRN. The prevalence of a CRP-albumin score (1 or 2) was significantly higher in the CRN group (40.0% or 30.9% versus 14.2% or 6.0%, respectively, P < 0.0001). In the multivariate logistic regression analysis, CRN was associated with male gender ( P = 0.01), disease duration ( P = 0.04), extensive colitis ( P = 0.03), concomitant primary sclerosing cholangitis ( P = 0.0003), median albumin levels ( P = 0.03), and an increased CRP-albumin score (score 1 or 2) ( P = 0.0002). Conclusions: Long-term serum inflammatory markers including the CRP-albumin score are associated with increased risk of CRN in patients with UC. Abstract : Article first published online 11 September 2015.